Virtual Reality Exposure Therapy on Alcohol and Nicotine: A Systematic Review. (November 2019) - Trahan, Mark H.; Maynard, Brandy R.; Smith, Kenneth Scott; Farina, Anne S. J.; Khoo, Yit Mui
Purpose: Virtual reality exposure therapy (VRET) is an intervention used to treat alcohol and nicotine dependence that delivers cue exposure therapy using a virtual reality environment; however, little is known about the effects of these interventions. Method: We used systematic review methods to examine the effects of VRET on alcohol or nicotine dependence, craving, and substance use with persons with current nicotine or alcohol dependence. We conducted a comprehensive search to retrieve published and unpublished intervention studies in 18 databases and other gray literature sources. Studies were screened, and data were extracted by two independent reviewers. Results: Five studies including 212 participants were included. Effects were found for alcohol and nicotine dependence and craving; however, significant methodological issues and high risk of bias were present across studies. Conclusion: Evidence of effects of VRET is sparse, and methodological flaws and gaps in reporting were identified. Implications for practice and research are discussed.